DEVOTION IN NICHOLAS SPARKSâ THE NOTEBOOK (1996): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - Fajarini, Yuli Andria (Kajian Linguistik dan Sastra, 2015)
The study described the devotion of Noah Calhoun, the main character in Nicholas Sparksâ The Notebook. It focused on its structural elements and the devotion of Noah to deal with inferiority feeling and compensation, striving for superiority, fictional finalism, style of life, social interest, and creative self that were explored through an individual psychological approach. This research was qualitative research with the primary data source of the novel entitled The Notebook written by Nicholas Sparks in1996. While the secondary data were other related sources. The data were collected through library research. The results showed that based on individual psychology analysis the major character, Noah Calhoun is psychologically affected. Noah fights hard to get his true love and shows her his devotion. He dedicates all of his life for Allie.Â Â Keywords: Devotion, The Notebook, Individual Psychological Approach.Â Â